Incidencia de resistencia bacteriana en pacientes con bacteriemia en el hospital teófilo dávila en el año 2018 - Correa Armijos, Cesar Augusto (Machala : Universidad Técnica de Machala, 2019)
Introduction: Bacteremia by any route of entry can complicate any clinical picture, hence the importance of analyzing the profiles of sensitivity and bacterial resistance in patients with bacteremia through statistical reviews of blood cultures for the initiation of empirical antibiotic therapy in a timely manner. Methodology and design: Cross-sectional study, not experimental, analytical and observational. This research is carried out following the guidelines of the academic degree process of the Technical University of Machala, within the Teófilo Dávila General Hospital of the city of Machala and the "Solidario" clinical analysis laboratory. Results: Total blood cultures 289, the majority were female patients, the most exposed group is between 18 to 64 years, with positive results of 5%. Of which 1% are by second intention. The most prevalent germs are Staphylococcus haemolyticus, Klesbsiella pneumoniae and Acinetobacter baumannii complex. Discussion: The incidence of complications, groups more exposed to blood cultures, the most common bacteria cultured, the agents related to high rates of bacteremia and mortality risk. Conclusions and Recommendations: The incidence of bacterial resistance in patients with bacteremia is 5%. The most common bacteria related to bacteremia and mortality high rates are: Staphylococcus haemolyticus and Klesbsiella pneumoniae. It is recommended for empirical antibiotic therapy, according to the profiles of sensitivity and resistance of the study, to Tigecycline and to avoid, according to clinical criteria, the use of ciprofloxacin and gentamicin.
Introducción: La bacteriemia por cualquier vía de entrada puede complicar cualquier cuadro clínico, de ahí la importancia de analizar los perfiles de sensibilidad y resistencia bacteriana en pacientes con bacteriemia mediante revisiones estadísticas de hemocultivos para el incicio de antibioticoterapia empirica de manera oportuna. Metodología y diseño: Estudio transversal, no experimental, analítico y observacional. Se realiza esta investigación siguiendo los lineamientos del proceso de titulación de la Universidad Técnica de Machala y laboratorio de análisis clínico "Solidario". Resultados: Total de hemocultivos: 289, la mayoría fueron de sexo femenino, el grupo más expuesto es el comprendido entre los 18 a 64 años, con resultados positivos del 5%. De los cuales el 1% son por segunda intención. Los gérmenes más prevalentes son Staphylococcus haemolyticus, Klebsiella pneumoniae y Acinetobacter baumannii complex. Discusión: La incidencia de complicaciones, grupos más expuestos a realizarse hemocultivos, las bacterias más comunes cultivadas, los agentes relacionados con altas tasas de bacteriemia y riesgo de mortalidad. Conclusiones y Recomendaciones: La incidencia de resistencia bacteriana en pacientes con bacteriemia es del 5%. Las bacterias más comunes y relacionadas con altas tasas de bacteriemia y mortalidad son: Staphylococcus haemoliticus y Klebsiella pneumoniae. Se recomienda para antibioticoterapia empírica, según los perfiles de sensibilidad y resistencia del estudio, a la Tigeciclina y evitar según criterio clínico el uso de ciprofloxacina y gentamicina.
Keywords: BACTERIEMIA; SENSIBILIDAD; RESISTENCIA BACTERIANA; HEMOCULTIVOS